การแสดงออกของอินเตอร์เฟอรอน-แกมมาในผู้ป่วยโรคไลเคนพลานัสในช่องปาก - พิมพ์พร รักพรม (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
Oral lichen planus (OLP) is a chronic inflammatory oral mucosal disease. Currently, the cause of OLP is still unknown, but cell-mediated immunity is implicated in the etiopathogenesis. Previous reports suggested that various cytokines which were produced by different cells in OLP lesion might have influence in the regulation of local immune response. Interferon-gamma (IFN- γ) is a proinflammatory cytokine which may be involved in the pathogenesis of OLP. The purpose of this study was to investigate the expression of IFN-γ in OLP by immunohistochemistry. Twenty OLP and 20 normal mucosa control tissue biopsies were sent for histopathologic examination to confirm diagnosis and immunohistochemical staining with antibody to IFN-γ. The results showed that positive reactivity to IFN-γ was detected in subepithelial mononuclear cells in 19 out of 20 OLP cases (95%), but was detected in keratinocytes in 5 out of 20 OLP cases (25%), Two out of 20 control cases (10%) revealed positive reactivity to IFN-γ in mononuclear cells, while all of the controls showed negative reactivity to IFN- γ in kerationcytes. However, the number of IFN-γ positive monuclear cells of OLP was statistically higher than that of normal mucosa (p – 0.000), whereas the number of keratinocytes positive to IFN-γ was not statistically higher than that of normal mucosa (p = 0.059). In addition, there were no statistical differences in the numbers of IFN-γ positive cells between erosive and atrophic OLP. These findings indicate that the increased expression of IFN-γ in the lesion may have an important role in the pathogenesis of OLP.